Tarian Tebe dalam Perspektif Teologi Publik: Makna Teologis Solidaritas dan Penerimaan terhadap Liyan - Ghari, Paskalis Rivaldo (Perspektif, 2025)
The Tebe dance, as one of the cultural heritages of the people of East Nusa Tenggara, particularly in Belu, represents not only an aesthetic artistic expression but also embodies profound social and spiritual dimensions. The circular formation in the Tebe dance symbolizes fraternity, togetherness, and solidarity, creating a space of encounter between individuals and the community, including relationships with the Other. This article aims to examine the theological meaning of the Tebe dance from the perspective of public theology and its relevance for Christian praxis in the social sphere. This study employs a qualitative approach through a theological–conceptual reflective method that integrates cultural analysis with the framework of public theology. The findings indicate that the Tebe dance can be understood as a symbol of faith praxis that embodies Gospel values such as solidarity, inclusivity, and openness to diversity within a pluralistic society. The dance presents a dialogical form of public theology rooted in local culture, in which faith is expressed not only within liturgical spaces but also through concrete social relationships. The scholarly contribution of this article lies in enriching the discourse of contextual public theology by offering a theological reading of local cultural practices as a medium for articulating and embodying a living and socially relevant faith.